2006
DOI: 10.1002/ange.200601317
|View full text |Cite
|
Sign up to set email alerts
|

Protons at Ice Surfaces

Abstract: Lieber obenauf: Untersuchungen zum Protonentransfer und H/D‐Austausch in Eisfilmen zeigen, dass sich das Proton vorrangig auf deren Oberfläche befindet. Es kann kurze Strecken mithilfe eines Staffel‐Hopping‐Mechanismus zurücklegen (siehe Bild), selbst wenn die Molekülbewegung weitgehend eingefroren ist. Diese Eigenschaften legen die Möglichkeit für protonenkatalysierte Reaktionen an kalten Eisoberflächen, z. B. auf interstellaren Staubpartikeln, nahe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The inability to use ion scattering to qualitatively check for interior proton mobility was partially overcome in a later study showing that protons released by HCl buried in ice are able to move to the ice surface. 73 The conclusion based on that new approach is also consistent with the isotopic exchange data for ice nanocrystals, which clearly show interior proton mobility in crystalline ice. 21,70 However, the response to adsorbates of the interior proton activity of nanocrystals as described above demonstrates that protons can move from the surface of ice to the interior at low temperatures, contradictory to interpretations of both the RIS 71,73 and the soft-landedproton data.…”
Section: Influence Of Surface Adsorbates On Interior and Surface Prot...supporting
confidence: 81%
See 2 more Smart Citations
“…The inability to use ion scattering to qualitatively check for interior proton mobility was partially overcome in a later study showing that protons released by HCl buried in ice are able to move to the ice surface. 73 The conclusion based on that new approach is also consistent with the isotopic exchange data for ice nanocrystals, which clearly show interior proton mobility in crystalline ice. 21,70 However, the response to adsorbates of the interior proton activity of nanocrystals as described above demonstrates that protons can move from the surface of ice to the interior at low temperatures, contradictory to interpretations of both the RIS 71,73 and the soft-landedproton data.…”
Section: Influence Of Surface Adsorbates On Interior and Surface Prot...supporting
confidence: 81%
“…73 The conclusion based on that new approach is also consistent with the isotopic exchange data for ice nanocrystals, which clearly show interior proton mobility in crystalline ice. 21,70 However, the response to adsorbates of the interior proton activity of nanocrystals as described above demonstrates that protons can move from the surface of ice to the interior at low temperatures, contradictory to interpretations of both the RIS 71,73 and the soft-landedproton data. 69 Computational results discussed above suggest that the activation barrier of the exchange process inside pure ice nanoparticles originates mostly from a combination of surface autoionization, and proton injection from the surface to the crystal interior.…”
Section: Influence Of Surface Adsorbates On Interior and Surface Prot...supporting
confidence: 81%
See 1 more Smart Citation
“…Finally Kang and co-workers 117 concluded that “the proton mobility issue is considered yet unresolved”. They report that vertical movement of protons in an ice film is possible below and above 140 K and the differences between lateral and vertical transport in ice might be explained through the thermodynamic affinity from protons to the ice surface 118, 119 . To summarize, there is no consensus value for the mobility of protons and deuterium in ice.…”
Section: Conduction Mechanism Coupled To Selectivitymentioning
confidence: 99%